Dialectical Processes of Health Framework as an Alternative to Social Determinants of Health Framework. - Friedman, Samuel R.; Walters, Suzan M.; Jordan, Ashly E.; Perlman, David C.; Nikolopoulos, Georgios K.; Mateu-Gelabert, Pedro; Rossi, Diana; Eisenberg-Guyot, Jerzy (American Journal of Public Health, 2025)
The social determinants of health (SDOH) framework has proven useful for research and practice in addressing the social causes of many health outcomes. However, its limitations may restrict its value as the world undergoes rapid ecological and social change. We argue that SDOH does not adequately incorporate rapidly changing or "far upstream" social processes (particularly social movements), the dialectics of social conflict and creative social innovation, or bidirectional causation. Ecosocial theory addresses some of these issues, yet dialectical frameworks offer additional insights during periods of rapid social change and disruption. The implications for research methods and practice are discussed.